PENGEMBANGAN MEDIA EDUKASI MAJALAH DIGITAL BERBASIS AUGMENTED REALITY DAERAHKU YANG BERSEJARAH DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 PADA PESERTA DIDIK KELAS V SDN 3 KENTENG - Rizka Dwi Asfia; Tri Astuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low 21st-century skills, particularly critical thinking and collaboration, among elementary students in learning science and social studies background the importance of technology-based media innovation. This study aims to develop and determine the effectiveness of an Augmented Reality (AR)-based digital magazine educational media on the topic